CuSn heterogeneous structure catalyst with carbon dioxide electro-catalysis reduction performance
By preparing CuSn heterogeneous structure catalyst, the problems of poor product selectivity and low yield in the electrocatalytic CO2 reduction process were solved, and efficient carbon dioxide reduction performance and low-cost catalytic effect were achieved.
Patent Information
- Application Number
- CN202410634426.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-21
- Publication Date
- 2025-04-25
AI Technical Summary
The existing Cu-based catalysts have problems of poor product selectivity and low yield during the electrocatalytic CO2 reduction process, and need to be modified to improve catalytic performance.
CuSn heterogeneous structure catalyst is used to prepare a Cu/Sn heterogeneous structure catalyst with electrocatalytic carbon dioxide reduction performance by stirring copper chloride dihydrate and sodium borohydride solution and quickly adding tin chloride solution to dihydrate, and a Cu/Sn heterogeneous structure catalyst with electrocatalytic carbon dioxide reduction performance is prepared by stirring, standing, centrifugation and drying.
It has achieved good electrocatalytic reduction of carbon dioxide at -0.9V, with a carbon monoxide production performance of up to 100%, and the catalyst structure is stable, has strong adsorption capacity, high electron transmission efficiency and low cost.
Smart Images

Figure HDA0004851246040000011 
Figure HDA0004851246040000012 
Figure HDA0004851246040000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field related to electrocatalysis, and in particular relates to a CuSn heterogeneous structure catalyst with electrocatalytic carbon dioxide reduction performance. Background Art
[0004] The electrochemical catalytic reduction of CO2 technology can reduce greenhouse gas CO2 into chemicals or fuels, such as CO, formic acid, ethanol, methane, ethane, etc., which can provide raw materials for the production of chemical products while alleviating environmental pressure.
[0005] Cu has a more suitable binding ability to the *CO intermediate, so it is easier for Cu to form *COH or *CHO intermediates through further reactions and promote CC coupling, so that subsequent reactions can proceed smoothly, and it is also easier to generate multi-electron transfer products. Because of Cu's unique ability to catalyze the production of multiple products, Cu-based catalysts are now widely used in the field of ECO2RR. However, Sn has a weak binding ability to the *COOH intermediate and is usually regarded as a typical metal for producing formic acid. However, when Cu and Sn are combined, it is found that they have excellent performance for reduction to CO.
[0006] Copper chloride and tin chloride are both important metal salts with good electrical and chemical properties, and have good electrocatalytic reduction performance for CO2 under electrocatalytic conditions. Although copper itself can produce a variety of products, the product selectivity is poor, making the yield of each product not very high. Other elements need to be introduced to modify it in order to improve its catalytic performance for CO2 and its selectivity for products. How to modify copper-based catalysts has become the current research focus. Summary of the invention
[0007] The purpose of the embodiments of the present invention is to provide a CuSn heterogeneous structure catalyst with electrocatalytic carbon dioxide reduction performance, aiming to solve the problems existing in the prior art pointed out in the background technology.
[0008] The embodiment of the present invention is implemented as follows: a method for preparing a Cu / Sn heterogeneous structure catalyst having electrocatalytic carbon dioxide reduction performance, comprising the following steps: uniformly dispersing cupric chloride dihydrate in deionized water. The cupric chloride dihydrate solution is vigorously stirred, and a sodium borohydride solution is slowly added at the same time. Then, a tin chloride dihydrate solution is quickly added thereto, vigorously stirred, and then allowed to stand for a period of time, washed, centrifuged, and dried to obtain a final Cu / Sn heterogeneous structure catalyst having electrocatalytic carbon dioxide reduction performance.
[0009] As another preferred embodiment of the present invention, the mass ratio of cupric chloride dihydrate to tin chloride dihydrate is 170:(11-180).
[0010] As another preferred embodiment of the present invention, the stirring time for preparing the CuSn heterogeneous structure catalyst with electrocatalytic carbon dioxide reduction performance is 2 to 15 minutes. The standing time for preparing the CuSn heterogeneous structure catalyst with electrocatalytic carbon dioxide reduction performance is 6 to 10 hours.
[0011] As another preferred embodiment of the present invention, during the centrifugation process, the sample is placed in a centrifuge, the speed is controlled to rise to 6000-8000 rpm at a rate of 10 rpm / s, and centrifuged at 6000-8000 rpm for 5-10 minutes.
[0012] As another preferred solution of the embodiment of the present invention, during the drying process, the product is placed in a vacuum drying oven at 60-80° C. for 8-12 hours.
[0013] As another preferred embodiment of the present invention, the molar ratio of cupric chloride dihydrate to tin chloride dihydrate is 100:(0.5-40).
[0014] Another object of the embodiment of the present invention is to provide a CuSn heterogeneous structure catalyst having electrocatalytic carbon dioxide reduction performance prepared by the above method.
[0015] As another preferred embodiment of the present invention, the CuSn heterogeneous structure catalyst has a diameter of 20nm to 200nm, and is a nanoparticle with a stable structure, good dispersion performance and uniform particle size. It has good performance in electrocatalytic reduction of carbon dioxide and photocatalytic degradation of dyes and antibiotics in water.
[0016] Another object of an embodiment of the present invention is to provide a CuSn heterogeneous structure catalyst with electrocatalytic carbon dioxide reduction performance prepared by the above method and used in reducing carbon dioxide.
[0017] The CuSn heterogeneous structure catalyst with electrocatalytic carbon dioxide reduction performance of the present invention has the characteristics of stable structure and strong adsorption capacity, which is conducive to the transmission of electrons; the preparation method of the present invention is simple, low in cost, and high in electrocatalytic efficiency. The prepared CuSn heterogeneous structure catalyst has good electrocatalytic carbon dioxide reduction performance at -0.9V, and the carbon monoxide production performance is as high as 100%. In addition, the CuSn heterogeneous structure catalyst with electrocatalytic performance of the present invention also has the characteristics of small dosage and non-toxicity. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The XRD spectrum of the optimal example CuSn-50 (the feed ratio of Cu element to Sn element is 50:1) heterogeneous structure catalyst;
[0019] Figure 2 This is the SEM image of the optimal example CuSn-50 (the feed ratio of Cu element to Sn element is 50:1) heterogeneous structure catalyst;
[0020] Figure 3 TEM, HRTEM and EDX images of the optimal example CuSn-50 (the feed ratio of Cu element to Sn element is 50:1) heterogeneous structure catalyst;
[0021] FIG4 is an electrochemical test diagram of the optimal example CuSn-50 (the feed ratio of Cu element to Sn element is 50:1) heterogeneous structure catalyst; DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0023] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0024] Example 1
[0025] This embodiment provides a CuSn heterogeneous structure catalyst having the performance of electrocatalytic reduction of carbon dioxide, and a preparation method thereof, comprising the following steps:
[0026] (1) While stirring 20 ml of 0.1 M copper chloride solution, add 60 ml of 0.1 M sodium borohydride solution to the solution. The solution changes from light blue to brown and then to black. Quickly add 20 ml of 2 mM tin chloride solution to the solution, stir vigorously for 2 min, and let stand for 8 h.
[0027] (2) The sample obtained after standing was centrifuged 5 times, and the centrifuge parameters were set to 6000 rpm. After centrifugation, it was placed in a 60° C. oven and dried for 8 h, and then a Cu / Sn heterogeneous structure catalyst with electrocatalytic reduction of carbon dioxide was obtained.
[0028] Example 2
[0029] This embodiment provides a CuSn heterogeneous structure catalyst having the performance of electrocatalytic reduction of carbon dioxide, and a preparation method thereof, comprising the following steps:
[0030] (1) While stirring 20 ml of 0.1 M copper chloride solution, add 60 ml of 0.1 M sodium borohydride solution to the solution. The solution changes from light blue to brown and then to black. Quickly add 20 ml of 0.5 mM tin chloride solution to the solution, stir vigorously for 10 min, and let stand for 10 h.
[0031] (2) The sample obtained after standing was centrifuged 5 times, and the centrifuge parameters were set to 7000 rpm. After centrifugation, it was placed in a 70° C. oven and dried for 11 hours, and then a CuSn heterogeneous structure catalyst with electrocatalytic reduction of carbon dioxide was obtained.
[0032] Example 3
[0033] This embodiment provides a CuSn heterogeneous structure catalyst having the performance of electrocatalytic reduction of carbon dioxide, and a preparation method thereof, comprising the following steps:
[0034] (1) While 20 ml of 0.1 M copper chloride solution is being stirred, 60 ml of 0.1 M sodium borohydride solution is added to the solution. The solution changes from light blue to brown and then to black. 20 ml of 1 mM tin chloride solution is then quickly added to the solution. The solution is stirred vigorously for 15 min and allowed to stand for 6 h.
[0035] (2) The sample obtained after standing was centrifuged 5 times, and the centrifuge parameters were set to 8000 rpm. After centrifugation, it was placed in an oven at 80° C. and dried for 10 hours, and then a CuSn heterogeneous structure catalyst with electrocatalytic reduction of carbon dioxide was obtained.
[0036] Example 4
[0037] This embodiment provides a CuSn heterogeneous structure catalyst having the performance of electrocatalytic reduction of carbon dioxide, and a preparation method thereof, comprising the following steps:
[0038] (1) While 20 ml of 0.1 M copper chloride solution is being stirred, 60 ml of 0.1 M sodium borohydride solution is added to the solution. The solution changes from light blue to brown and then to black. 20 ml of 20 mM tin chloride solution is then quickly added to the solution. The solution is stirred vigorously for 8 min and allowed to stand for 7 h.
[0039] (2) The sample obtained after standing was centrifuged 5 times, and the centrifuge parameters were set to 6000 rpm. After centrifugation, it was placed in a 70° C. oven for 12 hours to obtain a CuSn heterogeneous structure catalyst with electrocatalytic reduction of carbon dioxide.
[0040] Example 5
[0041] This embodiment provides a CuSn heterogeneous structure catalyst having the performance of electrocatalytic reduction of carbon dioxide, and a preparation method thereof, comprising the following steps:
[0042] (1) While stirring 20 ml of 0.1 M copper chloride solution, add 60 ml of 0.1 M sodium borohydride solution to the solution. The solution changes from light blue to brown and then to black. Quickly add 20 ml of 10 mM tin chloride solution to the solution, stir vigorously for 6 min, and let stand for 8 h.
[0043] (2) The sample obtained after standing was centrifuged 5 times, and the centrifuge parameters were set to 6000 rpm. After centrifugation, it was placed in a 70° C. oven and dried for 8 h, and then a CuSn heterogeneous structure catalyst with electrocatalytic reduction of carbon dioxide was obtained.
[0044] Example 6
[0045] This embodiment provides a CuSn heterogeneous structure catalyst having the performance of electrocatalytic reduction of carbon dioxide, and a preparation method thereof, comprising the following steps:
[0046] (1) While 20 ml of 0.1 M copper chloride solution is being stirred, 60 ml of 0.1 M sodium borohydride solution is added to the solution. The solution changes from light blue to brown and then to black. 20 ml of 10 mM tin chloride solution is then quickly added to the solution. The solution is stirred vigorously for 12 min and allowed to stand for 9 h.
[0047] (2) The sample obtained after standing was centrifuged 5 times, and the centrifuge parameters were set to 8000 rpm. After centrifugation, it was placed in an oven at 80° C. and dried for 12 hours, and then a CuSn heterogeneous structure catalyst with electrocatalytic reduction of carbon dioxide was obtained.
[0048] Example 7
[0049] This embodiment provides a CuSn heterogeneous structure catalyst having the performance of electrocatalytic reduction of carbon dioxide, and a preparation method thereof, comprising the following steps:
[0050] (1) While stirring 20 ml of 0.1 M copper chloride solution, add 60 ml of 0.1 M sodium borohydride solution to the solution. The solution changes from light blue to brown and then to black. Quickly add 20 ml of 2 mM tin chloride solution to the solution, stir vigorously for 2 min, and let stand for 8 h.
[0051] (2) The sample obtained after standing was centrifuged 5 times, and the centrifuge parameters were set to 6000 rpm. After centrifugation, it was placed in a 60° C. oven and dried for 8 h, and then a CuSn heterogeneous structure catalyst with electrocatalytic reduction of carbon dioxide was obtained.
[0052] Example 8
[0053] This embodiment provides a CuSn heterogeneous structure catalyst having the performance of electrocatalytic reduction of carbon dioxide, and a preparation method thereof, comprising the following steps:
[0054] (1) While 20 ml of 0.1 M copper chloride solution is being stirred, 60 ml of 0.1 M sodium borohydride solution is added to the solution. The solution changes from light blue to brown and then to black. 20 ml of 30 mM tin chloride solution is then quickly added to the solution. The solution is stirred vigorously for 8 min and allowed to stand for 9 h.
[0055] (2) The sample obtained after standing was centrifuged 5 times, and the centrifuge parameters were set to 8000 rpm. After centrifugation, it was placed in a 70° C. oven and dried for 9 hours, and then a CuSn heterogeneous structure catalyst with electrocatalytic reduction of carbon dioxide was obtained.
[0056] Example 9
[0057] This embodiment provides a CuSn heterogeneous structure catalyst having the performance of electrocatalytic reduction of carbon dioxide, and a preparation method thereof, comprising the following steps:
[0058] (1) While stirring 20 ml of 0.1 M copper chloride solution, add 60 ml of 0.1 M sodium borohydride solution to the solution. The solution changes from light blue to brown and then to black. Quickly add 20 ml of 40 mM tin chloride solution to the solution, stir vigorously for 2 min, and let stand for 8 h.
[0059] (2) The sample obtained after standing was centrifuged 5 times, and the centrifuge parameters were set to 6000 rpm. After centrifugation, it was placed in a 60° C. oven and dried for 8 h, and then a CuSn heterogeneous structure catalyst with electrocatalytic reduction of carbon dioxide was obtained.
[0060] Example 10
[0061] This embodiment provides a CuSn heterogeneous structure catalyst having the performance of electrocatalytic reduction of carbon dioxide, and a preparation method thereof, comprising the following steps:
[0062] (1) While 20 ml of 0.1 M copper chloride solution is being stirred, 60 ml of 0.1 M sodium borohydride solution is added to the solution. The solution changes from light blue to brown and then to black. 20 ml of 25 mM tin chloride solution is then quickly added to the solution. The solution is stirred vigorously for 6 min and then allowed to stand for 6 h.
[0063] (2) The sample obtained after standing was centrifuged 5 times, and the centrifuge parameters were set to 7000 rpm. After centrifugation, it was placed in an oven at 80° C. and dried for 12 hours, and then a CuSn heterogeneous structure catalyst with electrocatalytic reduction of carbon dioxide was obtained.
[0064] Figure 1It can be seen that the most abundant components in the catalyst are Cu2O and Cu;
[0065] Figure 2 It can be seen that the SEM image of the best example CuSn50 (the feed ratio of Cu element to Sn element is 50:1) catalyst prepared shows that two different nanoparticles are intertwined;
[0066] Figure 3 It can be seen that the TEM image of the best example CuSn50 (the feed ratio of Cu element to Sn element is 50:1) catalyst shows obvious heterogeneous interface, the HRTEM image can clearly show the lattice of Cu2O and Cu, and the EDX image can clearly reflect the presence of Cu element, O element and Sn element in the catalyst;
[0067] As can be seen from Figure 4, the electrochemical characterization of the optimal example CuSn50 (the feed ratio of Cu element to Sn element is 50:1) catalyst prepared shows that CuSn50 has a higher current density at the same voltage than other control groups; the current density in CO2 saturated solution is greater than that in N2 saturated solution, indicating that it has performance for CO2 reduction; under constant voltage, it can maintain good stability.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a CuSn heterogeneous structure catalyst, characterized in that: The following steps are involved: Copper chloride dihydrate is evenly dispersed in deionized water. The copper chloride dihydrate solution is vigorously stirred, and sodium borohydride solution is slowly added. Then, tin chloride dihydrate solution is quickly added thereto, stirred vigorously, and then allowed to stand for a period of time, washed, centrifuged, and dried to obtain the final CuSn heterogeneous structure catalyst.
2. The method for preparing the CuSn heterogeneous structure catalyst with electrocatalytic performance according to claim 1, characterized in that: The mass ratio of cupric chloride dihydrate to tin chloride dihydrate is 170:(11-180).
3. The method for preparing the CuSn heterogeneous structure catalyst with electrocatalytic performance according to claim 1, characterized in that: The stirring time for preparing the CuSn heterogeneous structure is 2 to 15 minutes. The standing time for preparing the CuSn heterogeneous structure is 6 to 10 hours.
4. The method for preparing the CuSn heterogeneous structure catalyst with electrocatalytic performance according to claim 1, characterized in that: During the centrifugal treatment, the sample is placed in a centrifuge, the speed is controlled to rise to 6000-8000 rpm at a rate of 10 rpm / s, and centrifuged at 6000-8000 rpm for 5-10 minutes.
5. The method for preparing the CuSn heterogeneous structure catalyst with electrocatalytic performance according to claim 1, characterized in that: During the drying process, the mixture is placed in a vacuum drying oven at 60 to 80° C. for 8 to 12 hours.
6. The method for preparing the CuSn heterogeneous structure catalyst with electrocatalytic performance according to claim 1, characterized in that: The molar ratio of cupric chloride dihydrate to tin chloride dihydrate is 100:(0.5-40).
7. The method for preparing the CuSn heterogeneous structure catalyst with electrocatalytic performance according to claim 1, characterized in that: The cupric chloride is cupric chloride dihydrate, and the tin chloride is tin chloride dihydrate.
8. A CuSn heterogeneous structure catalyst with electrocatalytic performance prepared by the method according to any one of claims 1 to 7.
9. The CuSn heterogeneous structure catalyst with electrocatalytic performance according to claim 8, characterized in that: The diameter of the CuSn heterogeneous structure catalyst is 20nm-200nm.
10. Use of the CuSn heterogeneous structure catalyst with electrocatalytic performance as claimed in claim 8 or 9 in reducing carbon dioxide.